Answer:
17 ± sqrt(337)
-----------------------
2
Explanation:
Let a = shorter leg
b= longer leg = a+7
c = hypotenuse = 2a-5
We can use the Pythagorean theorem
a^2+b^2 = c^2
a^2 + (a+7)^2 = (2a-5)^2
(a+7)^2 = a^2 +7a +7a+49 = a^2 +14a +49
(2a-5)^2 = 2a*2a -10a -10a +25 = 4a^2 -20a +25
Substituting these into the equation
a^2 + (a^2 +14a +49) = (4a^2 -20a +25)
Combine like terms
2a^2 +14a +49 = 4a^2 -20a +25
Subtracting 2a^2 from each side
2a^2 -2a^2 +14a +49 = 4a^2-2a^2 -20a +25
+14a +49 = 2a^2 -20a +25
Subtract 14a from each side
-14a+14a +49 = 2a^2 -20a -14a+25
+49 = 2a^2 -34a +25
Subtract 49 from each side
49-49 = 2a^2 -34a +25-49
0 = 2a^2 -34a -24
Divide each side by 2
0/2 = 2/2a^2 -34/2a -24/2
0 = a^2 -17a -12
Using the quadratic formula
a=1 b= -17 c = -12
17 ±sqrt( (-17)^2 - 4(1)(-12))
----------------------------------
2(1)
17 ± sqrt(337)
-----------------------
2